Memahami Konsep Meditasi Dalam Kajian Sutta-Sutta Dalam Suttapiṭaka - Fendy, Fendy; Surya, Julia; Angela, Shelfia; Suyati, Suyati; Lie, Nie (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya Wonogiri, 2023)
This article aims to explain the understanding of meditation, which is useful for achieving a state of perfect mental health, peace and tranquility. This is because not all have a complete understanding of meditation, on the contrary, the diversity of types of meditation has resulted in many perspectives on meditation, some of which are contrary to Buddhist teachings, such as meditation to gain wealth, attractive appearance, or supernatural powers. This research uses literature and literature review methods. Literature review with reference review, review of literature publications by previous researchers related to the topic to be researched. The author not only collects theories but various reference sources including journals, Buddhist scriptures and books. From the literature search, the discussion includes: types of meditation to train the mind, conditions that support meditation, the benefits of meditation, samatha bhavana and vipassana bhavana meditation practice, and also current meditation practices, as well as the implications of meditation practice for householders in everyday life as more and more the urgent need to be able to organize oneself better in facing various roles in the family, work and environment.